2021
DOI: 10.3390/cancers13184576
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Ferroptosis in Breast Cancer: Translational Implications Present and Future

Abstract: Breast cancer (BC) is the most common malignancy among women worldwide. The discovery of regulated cell death processes has enabled advances in the treatment of BC. In the past decade, ferroptosis, a new form of iron-dependent regulated cell death caused by excessive lipid peroxidation has been implicated in the development and therapeutic responses of BC. Intriguingly, the induction of ferroptosis acts to suppress conventional therapy-resistant cells, and to potentiate the effects of immunotherapy. As such, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 94 publications
(130 reference statements)
0
11
0
Order By: Relevance
“…Ferroptosis is a cell death form that is strongly correlated with lipid peroxidation and special modulators [ 26 ]. The cysteine metabolism and GPX4 inactivation have been proved to play important roles in ferroptosis [ 27 ]. Recent studies showed that it takes part in the process of some human diseases and cancers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a cell death form that is strongly correlated with lipid peroxidation and special modulators [ 26 ]. The cysteine metabolism and GPX4 inactivation have been proved to play important roles in ferroptosis [ 27 ]. Recent studies showed that it takes part in the process of some human diseases and cancers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically, ferroptotic cells show significant changes in mitochondrial morphology, with mitochondrial contraction, rupture of the outer mitochondrial membrane (OMM), and enlarged mitochondrial cristae. In the absence of swelling or contraction of cells in necrosis and apoptosis, neither nuclear changes nor chromatin condensation ( 3 , 66 , 67 ).…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%
“…The Tricarboxylic Acid (TCA) cycle and electron transport chain (ETC) action are necessary for mitochondria to produce sufficient ROS via oxidative phosphorylation (OXPHOS) ( 84 , 85 ). Ferroptotic cells undergo significant changes in mitochondrial morphology with mitochondrial contraction, rupture of the OMM, and enlarged mitochondrial cristae ( 3 , 67 ). Robustaflavone A (RF-A) promotes Voltage-dependent anion-selective channel protein 2 (VDAC2) expression and ubiquitinated degradation, inducing the breakdown of mitochondrial functional systems, lipid peroxidation and ROS production, ultimately leading to ferroptosis in breast cancer cells.…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%
“…Ferroptosis has the characteristics of inhibiting chemoresistance and enhancing antitumor immunity ( 18 ), which may be a potential strategy to overcome the drug resistance mechanism of traditional cancer treatments ( 12 ). Previous studies prove the feasibility of ferroptosis-related prognostic markers to predict overall survival and immune characteristics.…”
Section: Introductionmentioning
confidence: 99%